KEMAMPUAN BERPIKIR REFLEKTIF DITINJAU DARI SELF CONCEPT SISWA KELAS XI - Nur Isnaini; Zubaidah R; Dona Fitriawan; Agung Hartoyo; Halini Halini (UNIVERSITAS TANJUNGPURA, 2023)
This study aims to describe students' self-concept and reflective thinking skills. Quantitative descriptive is the research method used. Class XI students of SMA Negeri 8 Pontianak is the population used. The sample taken was class XI-C consisting of 32 students selected by purposive sampling. Self-concept questionnaires and tests of reflective thinking skills are the instruments used. Data were analyzed descriptively by using linearity, normality, and correlation tests. Based on the results of calculations using IBM SPSS statistics 25, it was obtained that the average self-concept and students' reflective thinking skills were 70.8% and 65.63% respectively, indicating that class XI-C students at SMA Negeri 8 Pontinak were included in the medium category. While the results of the Kendall's Tau correlation test obtained a significance level of 0.60 and a correlation coefficient of 0.246 and showed no relationship between self-concept and the ability to think reflectively.